2014
DOI: 10.1519/jsc.0000000000000338
|View full text |Cite
|
Sign up to set email alerts
|

The ACTN3 R577X Polymorphism Is Associated With Muscle Power in Male Japanese Athletes

Abstract: In this study, we investigated whether the ACTN3 R577X polymorphism is associated with muscular power in Japanese collegiate athletes by analyzing the mean and peak power results of a 30-second Wingate anaerobic test (WAnT) with respect to the ACTN3 R577X genotype in 253 Japanese athletes (144 men and 109 women). Each athlete performed a 30-second WAnT with a resistance equal to 7.5% of his or her body weight. Genotyping for the ACTN3 R577X (rs1815739) polymorphism was performed using the TaqMan approach. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
38
1
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 26 publications
4
38
1
1
Order By: Relevance
“…We also found that 4.6% of variability in the relative peak power in WAnT among male Japanese athletes was due to the ACTN3 R577X genotype [44]. Massidda et al [42] have reported that the ACTN3 R577X genotype accounts for 8.0% of the variation in squat-jump performance of elite soccer players.…”
Section: Effect Of Actn3 R577x Polymorphism On Athletic Performance Asupporting
confidence: 68%
See 3 more Smart Citations
“…We also found that 4.6% of variability in the relative peak power in WAnT among male Japanese athletes was due to the ACTN3 R577X genotype [44]. Massidda et al [42] have reported that the ACTN3 R577X genotype accounts for 8.0% of the variation in squat-jump performance of elite soccer players.…”
Section: Effect Of Actn3 R577x Polymorphism On Athletic Performance Asupporting
confidence: 68%
“…Yang et al [10] have reported that the ACTN3 XX genotype is associated with endurance performance only in female athletes. We detected a positive relationship between the ACTN3 R577X genotype and relative peak power in WAnT of Japanese male athletes but not in female athletes [44]. However, another study showed that the absence of ACTN3 negatively influenced peak isokinetic torque during knee extension in middle-aged women but not in middle-aged men [37].…”
Section: Effect Of Actn3 R577x Polymorphism On Athletic Performance Amentioning
confidence: 55%
See 2 more Smart Citations
“…There are contradictions in the results regarding the association between ACTN3 R577X genotype and sex differences in muscle phenotypes, e.g., strength and power of muscles [31,32]. It is revealed that ACTN3 XX genotype is associated with the manifestation of endurance only female athletes [25].…”
Section: Can Genotype Determine the Sports Phenotype?mentioning
confidence: 95%